Mitos Sawerigading (Epos Lagaligo): Suatu Analisis Struktural dan Penafsiran - Akhmad Akhmad; Usman Idris; Leo Siregar (ETNOSIA : Jurnal Etnografi Indonesia, 2018)
This article aims to analyze the myth of Sawerigading. The analysis approach is Structural Leivist analysis used to reveal the Structure in the myth of Sawerigading as a socio-cultural transformation and kinship structure to gain an understanding about the position of Sawerigading in the lagaligos epoch. The results show that the structure of Bugis-Makassar culture is always based on a divided binary opposition structure in three vertical parts, namely, upper structure, middle structure, and bottom. this structure originating from the cosmogini division transformed unconsciously and automatically into natural objects, house shape, and social stratification. Then, the existence of Sawerigading as a central character in the middle world is the result of the transformation of a limited exchange structure to the upper and the underworld kinship group through a marriage described as the foundation of the culture of Buginese and Makassarese people on earth. Liminal position on the myth of Sawerigading is a firm position to explain the reality of culture of the Buginese-Makassarese people. That is why the Buginese-Makassarese people have a strong and firm character.